Community-Based Support System in Suicide Prevention: Experiences from Indonesian Grassroots - Sriharini, Sriharini; Syamsiyatun, Siti; Suprianto, Agus; Sumarni (UIN Sunan Kalijaga Yogyakarta, 2024)
The community-based support system for suicide prevention was discovered using the qualitative analysis. In order to safeguard cases of suicide in person, twelve stakeholders were observed and interviewed about their experiences from Gunungkidul, Indonesia. This study finds that community-based assistance can be divided into three types of behaviours: responsiveness, localised healing, and empathy. Families provide security, comfort and acceptance. Public care is also offered to communities, including support and social institutions. Social advocacy and rehabilitation are CBOs program. It gives new perspective on suicide prevention, which is still primarily psychological approach and rarely employs integrative system to decrease suicide rates. Keywords: Community-Based Support System, Suicide Prevention, Mental Illness, Indonesian Grassroots Sistem dukungan berbasis komunitas untuk pencegahan bunuh diri ditemukan melalui analisis kualitatif. Untuk melindungi kasus bunuh diri secara langsung, dua belas pemangku kepentingan diobservasi dan diwawancarai mengenai pengalaman mereka di Gunungkidul, Indonesia. Penelitian ini menemukan bahwa bantuan berbasis komunitas dapat dibagi menjadi tiga jenis perilaku: responsivitas, penyembuhan lokal, dan empati. Keluarga memberikan rasa aman, kenyamanan, dan penerimaan. Perawatan publik juga ditawarkan kepada komunitas, termasuk dukungan dan institusi sosial. Advokasi sosial dan rehabilitasi adalah program dari organisasi berbasis komunitas (CBO). Ini memberikan perspektif baru dalam pencegahan bunuh diri, yang masih didominasi oleh pendekatan psikologis dan jarang menggunakan sistem integratif untuk menurunkan angka bunuh diri. Kata Kunci: Sistem Dukungan Berbasis Komunitas, Pencegahan Bunuh Diri, Gangguan Mental